Effects of different plantation years on grassland plant community in Maxian Mountain area of the Loess Plateau - Mao, Liang; Li, Jie; Ma, Xiao-Long; Quandahor, Peter; Gou, Yu-Ping (Frontiers in Plant Science, 2023)
The plant communities under the artificial afforestation forests in the Loess Plateau play an important role in fragile ecosystems restoration. Therefore, the composition, coverage, biomass, diversity, and similarity of grassland plant communities in different years of artificial afforestation in cultivated land were investigated. The effects of years of artificial afforestation on grassland plant community succession in the Loess Plateau were also investigated. The results showed that, as the number of years of artificial afforestation increased, grassland plant communities grew from the scratch, constantly optimized community components, improved community coverage, and increased above ground biomass. The community diversity index and similarity coefficient gradually approached those of a community that had been abandoned for 10 years and had recovered naturally. After 6 years of artificial afforestation, the dominant species of the grassland plant community changed from Agropyron cristatum to Kobresia myosuroides, and the main associated species changed from Compositae and Gramineae to Compositae, Gramineae, Rosaceae, and Leguminosae. The α diversity index accelerated restoration, Richness index and Diversity index increased, the Dominant index decreased. The Evenness index had no significant difference from CK. The β diversity index decreased as the number of years afforestation increased. The similarity coefficient between CK and grassland plant communities in various lands changed from medium dissimilarity to medium similarity 6 years of afforestation. According to the analysis of various indicators of grassland plant community, the grassland plant community had a positive succession within 10 years of artificial afforestation on the cultivated land of the Loess Plateau, and the threshold of the years from slow to fast was 6 years.